Africa Agriculture Transformation Scorecard: Performance and Lessons. Malawi - Jumbe, C.; Fakudze, Bhekiwe; Matchaya, Greenwell C.; Greffiths, Ikhothatseng Jacob; Musopole, R.; Kanyamuka, J.; Chinkhuntha, C.; Mwanaleza, E. (Regional Strategic Analysis and Knowledge Support System for Eastern and Southern Africa, 2023)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Three Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, and the third and most recent BR in 2021. This brief draws on the third BR report to summarize the performance of Malawi in pursuit of the seven Malabo Declaration commitments across the three BR cycles, highlights challenges and lessons from the third BR, and outlines policy and programmatic measures required for the country to meet the Malabo Declaration commitment targets by 2025. The third BR shows that Malawi is currently off-track to meet its 2025 targets under the Malabo Declaration. This is a step back from the first BR, which showed Malawi on course to meet four of the seven Malabo commitments. However, even though off-track, the country is rated as progressing well toward achieving the Malabo targets. A key recommendation from the analysis is for Malawi to further open up to intra-regional trade by utilizing structured markets and adding value to its agricultural products. Fostering regional trade will increase incomes and reduce poverty.